BIlingüismo social en Bolzano: análisis de las actitudes lingüísticas (2020)
The Trentino-Alto Adige region has been subject to several studies on bilingualism. This territory belonged to Austria until 1919 when it became part of the Republic of Italy due to its victory in the First World War. This event changed the dynamics of a traditionally Germanic region, where measures were taken in order to Italianize it. Despite these measures, the German-speaking group and the emerging Italian-speaking group remain culturally separated while inhabiting the same territory. One of the places where changes in the linguistic composition have been most evident is Bolzano, the capital city of the province, where efforts to promote bilingualism in the region have been heavy. Since the Second Statute of Autonomy of 1972, it has sought to preserve the traditions of both linguistic groups, making the region an officially bilingual territory. This linguistic distinction has led to the development of diverse research on bilingualism, such as the KOLIPSI I and KOLIPSI II projects, especially focused on the acquisition of the German and Italian languages. However, to date no studies have been carried out on language attitudes in this region, which gives rise to the objective of this research: to know the effect of language attitudes in the development of social bilingualism in Bolzano and its surrounding areas. In order to achieve this goal, a sociolinguistic survey, semistructured-interviews, a matched-guise test, participant observation, and social cartography were used, all of them supported by a fieldwork diary. The sociolinguistic survey gave a general idea of the linguistic profiles of the participants and the use of each language. The interviews revealed the perceptions and explicit opinions of the speakers regarding the linguistic situation of the region and the contact they had with the other linguistic group. The matched-guise test was used to investigate the participants’ perceptions and reactions to linguistic stimuli in German, Italian, and South Tyrolean, a dialect of German. The social cartography exercise was used in order to recognize the incidence of migration mainly in the twentieth century on the speaker’s perception of languages. The participant observation complemented and corroborated the results obtained with the other techniques, assuming that speakers may not reflect their attitudes when they are aware of being part of a research project. In the results it can be observed that language attitudes are favorable towards Italian and German from both linguistic groups, with a tendency to be more positive from the German linguistic group. This is the first study to address language attitudes of the inhabitants of the city of Bolzano and its surrounding areas in relationship with migration, ethnic identity, and linguistic discrimination. It is also the first study in which the matched-guise test is put into practice in Bolzano.